Estimates and Methods of Damage from Man-Caused Emergencies of Situations at Hazardous Production Facilities of the Republic of Uzbekistan (Zien Journal of Social Sciences and Humanities, 2023)
Risk assessment in a certain territory, including calculations of the possible number of dead (injured) people and economic losses that may be caused by hazardous phenomena, is carried out on the basis of an analysis of the danger of the territory, threats to people and objects, their vulnerability and possible damage. The article reveals the concept of damage and methods for its assessment from a hypothetical and real accident